2009
DOI: 10.1073/pnas.0810304106
|View full text |Cite
|
Sign up to set email alerts
|

Suppressor of gamma response 1 ( SOG1 ) encodes a putative transcription factor governing multiple responses to DNA damage

Abstract: The Arabidopsis sog1-1 (suppressor of gamma response) mutant was originally isolated as a second-site suppressor of the radiosensitive phenotype of seeds defective in the repair endonuclease XPF. Here, we report that SOG1 encodes a putative transcription factor. This gene is a member of the NAC domain [petunia NAM (no apical meristem) and Arabidopsis ATAF1,2 and CUC2] family (a family of proteins unique to land plants). Hundreds of genes are normally up-regulated in Arabidopsis within an hour of treatment with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
335
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 240 publications
(353 citation statements)
references
References 26 publications
15
335
0
Order By: Relevance
“…At the same time, it was previously found that upregulation of CYCB1;1 after DNA damage requires SOG1 (Yoshiyama et al , 2009). Here, we have shown that SOG1 binds to the promoter of CYCB1;1 and hence appears to directly activate its expression presumably promoting CDKB1 activity and the execution of HR.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…At the same time, it was previously found that upregulation of CYCB1;1 after DNA damage requires SOG1 (Yoshiyama et al , 2009). Here, we have shown that SOG1 binds to the promoter of CYCB1;1 and hence appears to directly activate its expression presumably promoting CDKB1 activity and the execution of HR.…”
Section: Discussionmentioning
confidence: 80%
“…Previously, it was found that CYCB1;1 upregulation depends on ATM and SOG1 (Culligan et al , 2006; Yoshiyama et al , 2009). To test therefore whether CYCB1;1 and CDKB1s are directly regulated by SOG1, we performed ChIP experiments with plants expressing a tagged SOG1 version grown on cisplatin.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Members of this subgroup contain an Nterminal extension of the NAC domain (Fig. 1B) and have diverse functions in e.g., responses to DNA damage (SOG1) 24 and secondary cell wall development Bank accession 1UT7) followed by a disordered C-terminus (different conformers in gray) encompassing transcription regulatory activity and a large interaction potential. 10 (B) Predicted disorder plotted as a function of alignment position for representative NAC proteins.…”
mentioning
confidence: 99%